Theoretical Study of the Substituent and Nitrogen Number Effects on the Uranium Binding Selectivity of Crown Ethers - Saprizal Hadisaputra; Agus Abhi Purwoko; Ria Armunanto; Harno Dwi Pranowo (Acta Chimica Asiana, 2020)
The compounds, [UO2(dibenzo-18-crown-6)]2+ and [UO2(18-crown-6)]2+, as well as their related complexes: numerous disubstituted dibenzo-18-crown-6 and azacrown complexes are studied using density functional theory (DFT). Quasi-relativistic effective core potentials developed in the Stuttgart and Dresden groups was used together with the accompanying basis set for uranium and DZP basis set was used for crown ether atoms. The effects of substituent and nitrogen number on the binding selectivity were discussed in term of the structural parameter, atomic charge and interaction energy, thermodynamic parameters, and charge transfer. The electron donating substituents increase the capability of dibenzo-18-crown-6 toward UO22+ ion. In contrast, the electron withdrawing substituents have the opposite effect. It clearly shows that UO22+ prefers N donor recognition. For the systems involved, the result shows that the hexaaza-18-crown-6 exhibits the largest metal interaction capability to UO22+ ion. The calculated results are in a good agreement with the experimental values.